DEVELOPMENT AND CHARACTERIZATION OF GASTRO RETENTIVE MUCOADHESIVE MICROBEADS CONTAINING SIMVASTATIN WITH DIFFERENT CROSS LINKING AGENTS - K., VENKATA RAMANA REDDY; M. V., NAGABHUSHANAM; B., PAMULA REDDY; E., RAVINDAR NAIK (International Journal of Applied Pharmaceutics, 2020)
Objective: The aim of the present work was to prepare and examine drug release of the oral controlled release microbeads using different curing agents by emulsification internal ionic gelation technique. Methods: Cross-linked alginate microbeads were prepared with different cross linking agents by using mucoadhesive properties. The formation and compatibility of microbeads were confirmed by compatibility studies. Prepared microbeads evaluated for encapsulated efficiency, micromeritic properties, drug loading, in vitro wash off studies, in vitro dissolution studies, drug release kinetics and stability studies Results: The in vitro drug release was influenced by both type of curing agents and type of polymers and no significant changes in characterization parameters was observed after 3 mo stability studies. The sustained release profile of optimized batch was found to be 99.66±0.18% in comparison to pure drug profile of 28.64±0.02% at 12 h release study. Results of both wash-off and in vitro studies suggests that batch (SF2) prepared with aluminium chloride has shown better mucoadhesive property. Drug release of optimized batch follows zero order with non fickian mechanism according to Korsmeyer-Peppas equation. Conclusion: The data suggest the use of simvastatin mucoadhesive cross linked microbeads to offer the potential for oral controlled drug delivery with improved gastric retention and capable to provide sustained drug release by using cross linking agents.